DEVOLOPMENT OF COMPOSITION AND TECHNOLOGY OF EYE MEDICINAL FILMS WITH ALOE EXTRACT - Y. V. Shikova; V. A. Lichoded; A. V. Brazhenko; Z. R. Ishmakova; I. F. Girfanov (Фармация и фармакология (Пятигорск), 2016)
Drugs which stimulate cornea regeneration are an obligatory component of the inflammatory diseases and injuries of eyes treatment. Nowadays the choice for these drugs is not diverse. A search for new prolonged medical drugs in dosage forms of eye films with Aloe extract with germicide and regenerative properties is prospective nowadays. A choice for additive substances for production of eye films with Aloe extract and working out of an optimal extraction technology was the purpose of the study. Materials and methods. The work involved: Aloe liquid extract, methylcellulose (MC), polyvin-ylpyrrolidone (PVP), carboxymethylcellulose (CMC), glycerol plasticiser, polyethylene-400. Humidity of ophthalmic drug films was determined with a gravimetric method; films dimensions: thickness, length and width in mm were measured with calipers; pH of the aqueous solution in films was determined potentiometrically. Results and discussion. A satisfactory appearance (uniformity, goodgap from the substrate, the absence of cracks and ruptures, elasticity and film thickness) was the criterion for selection of film formers at the initial stage. Based on the requirements for ocular dosage forms, the films included sodium tetraborate buffer solution, which provided stability during preparation and use. Based on the study of literature data the selected samples were administered with 10% of aloe liquid extract. Prepared homogeneous transparent polymer solutions were cast on glass petri dish, pretreated with ethyl alcohol layer with a thickness of 5 mm. Drying of the film mass was done at room temperature to a residual humidity of 5%. As the result of the studies we have chosen films with film former of methylcellulose. Plates were strong, elastic, homogeneous, without gaps transparencies odorless, 0.035 mm thick. The obtained films were carved oval shape with a scalpel 4.0 mm in width and 9 mm diameter. Conclusions. 1. We have designed an optimal structure and technology of ocular medicinal films with Aloe extract. 2. Based on the analysis of the data we have found that the worked out base fulfills all the physical, chemical, and technological parameters.